The Effect of Deep Breathing combined with Spiritual Emotional Freedom Technique (DB-SEFT) Therapy in Reducing Anger Behavior Among the Elderly at Sentra Terpadu Pangudi Luhur Bekasi Indonesia - Nurfauziah, Nisa Almalia; Susilawati, Susilawati; Kartika, Tuti (Westscience Press, 2025)
Anger behavior in the elderly must be addressed due to its negative impact on physical, psychological, and social well-being. Recurrent anger can disrupt social relationships, trigger chronic stress, and reduce overall quality of live. One potential solution to manage this problem is phychosocial therapy. This study investigates the effectiveness of DB-SEFT therapy (Deep Breathing combined with Spiritual Emotional Freedom Technique) in reducing anger behavior among the elderly. A quantitative approach with an experimental method was used, employing a Single Subject Design (SSD) with a Reversal A-B-A model. Data were collected through tally behavior observation sheet focused on specific anger behaviors such as yelling, insulting, grumbling, and throwing objects. DB-SEFT therapy integrates deep breathing, dzikir (Islamic chanting), and prayer with the SEFT steps: setup, tune-in, and tapping—modified to suit the elderly. The participants were older adults living at Sentra Terpadu Pangudi Luhur (STPL) Bekasi, Indonesia. Findings revealed a decrease in the frequency of anger behaviors following the intervention, as shown through graphical trend analysis and comparisons within and between conditions. The therapy is simple, adaptable, and can be practiced independently or with assistance from a therapist. DB-SEFT is recommended as an alternative psychosocial intervention for reducing anger in the elderly.